Pengaruh Dimensi Brand Equity Dan Brand Trust Terhadap Loyalitas Pelanggan Pada Produk Kosmetik Merek Make Over Di Kota Padang - Indah Eka Putri; Afriyeni Afriyeni (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2023)
The purpose of this study was to determine and analyze the effect of the dimensions of brand equity and brand trust on customer loyalty to the Make Over brand of cosmetic products in the city of Padang. The population in this study were all customers of the Make Over brand of cosmetics in the city of Padang. Determining the number of samples using the Cochran formula, the number of respondents as samples in this study were 96 respondents. The data analysis technique used is multiple linear regression analysis and for hypothesis testing using statistical t test. The results showed that: Brand awareness, brand association, perceived quality and brand trust had a significant effect on customer loyalty to the Make Over brand of cosmetic products in the city of Padang. Meanwhile, brand loyalty have no effect on customer loyalty to Make Over brand cosmetic products in Padang City. So it is suggested to the management to continue to pay attention to brand awareness, brand association, perceived quality, and brand trust. This is because brand awareness, brand association, perceived quality, and brand trust have a significant influence on customer loyalty.